2022
DOI: 10.1590/1806-9061-2021-1615
|View full text |Cite
|
Sign up to set email alerts
|

Male Layer-Type Chickens - an Alternative Source for High Quality Poultry Meat: a Review on the Carcass Composition, Sensory Characteristics and Nutritional Profile

Abstract: Male layer-type chickens are usually killed immediately after hatching. Despite the ethical debates and the sharp criticism against this practice, it is still widely applied. One of the possible alternatives for the culling of layer cockerels might be their use for meat production. Except for a small market niche, meat from male layer-type chickens is not currently popular among wider circles of consumers. However, although rather scarce, research on this type of bird shows that in comparison to fast or slow g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
5
1
1
Order By: Relevance
“…Many authors have shown that the textural characteristics of the pectoral muscle are influenced by genotype, age of the birds, sex, nutrition and handling of carcasses after slaughter [11,26,38,39]. In our study, the genotype of the birds did not significantly affect the texture characteristics of the pectoralis major muscle.…”
Section: Discussioncontrasting
confidence: 45%
“…Many authors have shown that the textural characteristics of the pectoral muscle are influenced by genotype, age of the birds, sex, nutrition and handling of carcasses after slaughter [11,26,38,39]. In our study, the genotype of the birds did not significantly affect the texture characteristics of the pectoralis major muscle.…”
Section: Discussioncontrasting
confidence: 45%
“…France and Germany are the first countries to implement this ban, starting in 2022. Consequently, alternative strategies, such as appropriate breeding methods, must be explored to utilize male layer-type chickens for meat production [5]. This shift could potentially create a market gap due to the limited availability of parent lines capable of producing layertype chickens suitable for alternative rearing systems or floor-raising.…”
Section: Introductionmentioning
confidence: 99%
“…This import aimed to establish a new line, BB, which is currently part of the country's gene pool. The researchers are * Corresponding author: nkolevphd@gmail.com focused on developing a dual-purpose crossbreed based on the Bresse Gauloise breed, where females are bred for egg production and males for meat [1,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative source of this meat could be male layer-type chickens. In fact, their rearing for meat has been considered as an option in addition to in ovo sex determination and the development of dual-purpose breeds to avoid the common practice of culling them immediately after hatching [10]. Based on previous studies, showing that the meat of male layer-type chickens is not inferior to fast-and slow-growing chickens, we focused on their age at slaughter as a factor to produce high-quality meat and meat products, as well as achieve more economically efficient production.…”
Section: Introductionmentioning
confidence: 99%